Kajian Terkait Pelayanan Rumah Sakit di Indonesia - Ambarsari, Dessy (STIE AUB Surakarta)
This article was prepared with the aim to provide an overview related to hospital services in Indonesia. Previous studies used as literature in this study, to see hospital services in Indonesia. Satisfaction is one of the hospital services objectives. Hospital services need to be reviewed by discussing in various aspects. Hospital services is not a stand-alone. Hospital services related to human resources management, facilities and administrative aspects. Hospital services which consist of a variety factors can make the consideration for the hospital management to formulate policies related to hospital services. Policy formulation is expected to consider various factors that may influence the hospital services. Keywords: services, hospitals, performance, satisfaction